Characteristics of Waste Cooking Oil in Denpasar - Yuarini, Dewa Ayu Anom; Putra, G.P. Ganda; Wrasiati, Luh Putu; Wiranatha, A.A.P.A Suryawan (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 1 (2018): Scientific Journal of Food Technology, 2018)
This study aims to determine the characteristics of waste cooking oil in Denpasar to be known the quality of waste cooking oil so that utilization is not for consumption again but processed into non-food products with the appropriate preliminary treatment. The population in this research is all waste cooking oil produced in Denpasar city. Determination of research sample was done by using purposive sampling method with some consideration such as (1)Choice of hotel and restaurant with average occupancy above 70%/year, (2) Street food vendors and street snack vendors with daily proccess using 10 L cooking oil a day. So that obtained 21 samples of waste cooking oil from the three sources of sampling. The observed variables are water content, peroxide number and free fatty acid. The results showed that waste cooking oil which has the highest water content from the street food vendor amount 0,40%, while the lowest from hotel/restaurant amount 0,09%. The highest peroxide rate were obtained on street snack vendors amount 13,27 MeqO2/1000 while the lowest were hotel/restaurant amount 12,76 MeqO2/1000. The highest free fatty acids were obtained by street food vendor amount 0,35%, while the lowest from hotel/restaurant amount 0,19%.